Hydrogenation catalyst, preparation method thereof and application of hydrogenation catalyst in preparation of toluenediamine by hydrogenation of dinitrotoluene

By using sodium oleate modified thermally sensitive polymer modified nanosilicon coated molecular sieve support and resource-recycled metal active components in the catalyst, the problems of high cost, easy carbon deposition and safety hazards in the production of toluene diamine are solved, and efficient and stable catalytic effects are achieved.

CN119793518APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510001437.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing catalysts have high costs, easy carbon deposition, harsh reaction conditions and safety hazards in the production of toluenediamine.

Method used

A nano-silicon coated molecular sieve carrier modified with sodium oleate modified heat-sensitive polymer was used as a support, and supported metal active components such as Ni, Cr, Sc, and Zn. The metal components in the waste catalyst were recycled and utilized to prepare an efficient hydrogenation catalyst.

Benefits of technology

High catalytic activity and good stability are achieved, production costs are reduced, tar generation is avoided, the selectivity of toluene diamine is improved, and the safety hazards of catalysts are solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a hydrogenation catalyst, a preparation method thereof and application of the hydrogenation catalyst in preparation of toluenediamine by hydrogenation of dinitrotoluene. The catalyst comprises a sodium oleate modified thermosensitive polymer modified nano silicon coated molecular sieve carrier, and metal active components Ni and Cr and auxiliary components Sc and Zn which are loaded on the carrier. The catalyst provided by the invention has the advantage of molecular sieve structure stability, the high dispersibility and larger specific surface area of the nano silicon material, and is beneficial to exposure of a metal active center, and the surfactant characteristic of the sodium oleate modified thermosensitive polymer material, so that the pressure drop of a catalyst bed is reduced, and the carbon deposition resistance of the catalyst is improved. According to the preparation method of the catalyst, resource recycling of two kinds of device dangerous waste is achieved, the activity and selectivity of the nitrobenzene hydrogenation catalyst are improved, generation of tar is effectively inhibited, and the catalyst shows good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic hydrogenation, and specifically relates to a hydrogenation catalyst, a preparation method of the catalyst, and a method for preparing toluenediamine by hydrogenating dinitrotoluene in a fixed bed. Background Art

[0002] Toluenediamine is an important aromatic amine compound, often used as the main raw material for the production of polyurethane, and synthesized into toluene diisocyanate through phosgenation. As an intermediate for fine chemicals, it is widely used in rubber, petroleum, chemical, textile, medicine and other fields. In recent years, with the construction of TDI units and the continuous expansion of production scale, the demand for toluenediamine has increased, and the market potential is huge.

[0003] The catalytic hydrogenation of dinitrotoluene is currently the most important method for producing toluenediamine in the industry due to its high conversion rate and high selectivity for toluenediamine. At present, the industrial production of toluenediamine generally uses a supported Pd, Pt and other precious metal catalysts or a Raney nickel catalyst to catalyze the hydrogenation of dinitrotoluene. The supported precious metal catalyst has high activity in the hydrogenation reaction of nitrobenzene compounds, but the production and application cost is high, and it is easy to be deactivated by carbon deposition. The reaction temperature and pressure of the Raney nickel catalyst are high, and the reaction conditions are demanding. The equipment investment is large, and the catalyst is prone to spontaneous combustion, which poses a certain degree of safety hazard. The supported nickel catalyst can exert catalytic activity at a lower reaction pressure, the reaction conditions are mild, and it has a price advantage.

[0004] Patent CN 114588941B discloses a method for preparing a Pt-based catalyst supported on a modified molecular sieve carrier. The catalyst recycles precious metals in the ash from the incineration of aniline tar. The catalyst has the advantages of high activity and long life, but the production of the catalyst still requires the addition of Pt precious metals, which is costly. Patent CN107233887B discloses a method for preparing a toluenediamine catalyst by reduction magnetization of laterite nickel ore. The catalyst preparation process is relatively simple, but the impurity metal content in the catalyst is high and the catalyst activity is insufficient, resulting in low dinitrotoluene conversion rate and toluenediamine selectivity.

[0005] The catalysts referred to in the above-mentioned preparation process, Pd and Pt precious metal catalysts are relatively expensive, and have the disadvantages of easily inducing side reactions and being easily coked and deactivated due to local overheating; the Raney nickel reaction conditions in nickel-based catalysts are harsh and there are safety hazards. The current catalyst preparation process for resource recovery of metallic nickel has problems such as complicated process, low recovery rate, and insufficient catalyst reaction activity. Summary of the invention

[0006] The present invention aims to solve the shortcomings of the prior art and provides a hydrogenation catalyst and a preparation method thereof. The catalyst preparation method can realize the resource recycling of hazardous wastes from two devices.

[0007] The present invention also provides application of the catalyst in hydrogenating dinitrotoluene to prepare toluenediamine, which can effectively inhibit tar generation and exhibits high catalytic activity and good stability.

[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0009] In a first aspect, the present invention provides a hydrogenation catalyst, which includes a nano-silicon coated molecular sieve carrier modified by a sodium oleate-modified thermosensitive polymer, and a metal active component loaded on the carrier, wherein the metal active component includes Ni, Cr, Sc, Zn or its oxides.

[0010] In one embodiment, in the hydrogenation catalyst, based on the total weight of the catalyst, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier accounts for 50-90wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, etc.;

[0011] The content of the metal active components loaded on the carrier is calculated as metal elements, respectively: Ni 10-40wt%, preferably 20-30wt%; Cr 0.2-5wt%, preferably 1-3wt%; Sc 0.1-3wt%, preferably 0.5-1wt%; Zn 0.01-0.3wt%, preferably 0.05-0.1wt%; specifically, Ni can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and the like; Cr can be 0.2wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% and the like; Sc can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% and the like; Zn can be 0.01wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt% and the like.

[0012] In one embodiment, the hydrogenation catalyst has a specific surface area of ​​400-800m 2 / g, for example 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g, etc., and the pore size is 25-50nm, for example, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc.

[0013] In one embodiment, in the hydrogenation catalyst, the grain size of the metal active component Ni is 1-5 nm, and the grain size of Cr is 2-7 nm.

[0014] In one embodiment, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier in the hydrogenation catalyst can be prepared by the following method, specifically, comprising the following steps:

[0015] (1) placing the molecular sieve in a gas phase reactor, introducing trisilane and nitrogen, maintaining a certain temperature and pressure for vapor phase deposition reaction, and obtaining a nano-silicon coated molecular sieve carrier;

[0016] (2) dispersing the nano-silicon coated molecular sieve carrier in an aqueous solution of isopropyl acrylamide, adding ammonium persulfate and sodium oleate, stirring under the protection of an inert atmosphere, filtering, washing and drying to obtain a nano-silicon coated molecular sieve carrier modified by a sodium oleate-modified thermosensitive polymer.

[0017] In a specific embodiment, the molecular sieve in step (1) is selected from one or more of 13X molecular sieve, Y molecular sieve, and ZSM-5 molecular sieve, preferably Y molecular sieve.

[0018] In a specific embodiment, the volume ratio of trisilane to nitrogen in step (1) is 0.2-5:1, preferably 0.5-2:1, and the trisilane is converted into a gas phase and then introduced into a gas phase reactor;

[0019] Specifically, the amount of trisilane / nitrogen introduced controls the reaction pressure to be within a desired range.

[0020] In a specific embodiment, the vapor deposition reaction in step (1) is carried out at a temperature of 150° C.-1500° C., a pressure of 0-1.0 MPaG, and a time of 10-90 min.

[0021] In a specific embodiment, the mass ratio of the isopropyl acrylamide to the nano-silicon coated molecular sieve carrier in step (2) is 0.1-10:1, preferably 0.2-3:1;

[0022] Preferably, the aqueous solution of isopropylacrylamide has a concentration of 50-80 wt %.

[0023] In a specific embodiment, the mass ratio of the ammonium persulfate to the nano-silicon coated molecular sieve carrier in step (2) is 0.05-2:1, preferably 0.1-0.5:1.

[0024] In a specific embodiment, the mass ratio of the sodium oleate to the nano-silicon coated molecular sieve carrier in step (2) is 0.05-1:1, preferably 0.1-0.5:1.

[0025] The preparation of the above-mentioned sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier, step 2) also includes stirring under the protection of an inert atmosphere (such as nitrogen, argon, etc.), filtering, washing and drying, which are all conventional operations in the field and are not specifically required here.

[0026] In a second aspect, the present invention provides a method for preparing the above-mentioned hydrogenation catalyst.

[0027] The hydrogenation catalyst of the present invention is a molecular sieve supported catalyst, which has been involved in the prior art and can be prepared by loading active components using existing processes and conventional methods in the art. The operation and process conditions of the present invention, as well as the devices used therein, can be selected according to the corresponding conventional methods in the art, and there is no particular limitation on this.

[0028] For example, in one embodiment, the method for preparing the hydrogenation catalyst comprises the following steps:

[0029] A solution containing metal active elements is added to a nano-silicon coated molecular sieve carrier modified by a sodium oleate-modified thermosensitive polymer, and a catalyst precursor is obtained by ultrasonic impregnation and drying.

[0030] The catalyst precursor and the binder are mixed evenly, pressed into tablets, ground and sieved, dried, and calcined to obtain the hydrogenation catalyst.

[0031] In a specific embodiment, the metal active elements are nickel, chromium, scandium and zinc;

[0032] The salt solution containing metal active elements described in the present invention can be a soluble salt solution of nickel, chromium, scandium and zinc, such as an aqueous solution of nickel nitrate, chromium nitrate, scandium nitrate and zinc nitrate; wherein the ratio of the metal elements must meet the content specified by the catalyst metal active components described above, for example, the mass ratio of Ni to Cr, Sc, and Zn elements is (10-60): (0.2-5): (0.1-3): (0.01-0.3); the method of using metal soluble salts as active metal precursors is a conventional operation in the field, and the specific operation and reaction conditions can be combined and screened by technicians based on the existing technology according to the target catalyst product, and the present invention will not be repeated here.

[0033] In a specific embodiment, the salt solution containing metal active elements can be a salt solution containing metal active elements obtained by resource recovery.

[0034] The nickel metal element is derived from a nickel-based waste catalyst, such as a nickel-based waste catalyst produced by a toluene diamine device; the solution containing nickel salt recovered thereby is a nickel oxalate solution, wherein the nickel oxalate preferably has a concentration of 40-55 wt%, and the solvent includes water;

[0035] Specifically, the nickel-based waste catalyst produced by the toluene diamine device is produced in the production process of dinitrotoluene hydrogenation to toluene diamine. Since the activity of the catalyst decreases with the increase of the operating time of the device, the waste catalyst needs to be discharged regularly. The particle size of the waste catalyst becomes smaller after wear and the skeleton structure is lost, which makes it difficult to reuse the system. As hazardous waste, the treatment method is complicated, but the waste catalyst usually contains 20-80wt% of Ni element, which can be used as the precursor of the active component of the catalyst of the present invention. For example, a method for treating nickel-based waste catalyst to obtain nickel oxalate solution is to mix the waste catalyst with oxalic acid, heat and stir to react, filter and take the clear liquid, and prepare;

[0036] Preferably, the mass ratio of the waste catalyst to oxalic acid is 2-10:1, preferably 3-5:1; preferably, the heating temperature is 60-100° C.; preferably, the reaction time is 1-4 h.

[0037] Preferably, the mass ratio of the nickel oxalate salt solution to the carrier is 0.6-3:1, preferably 1-2:1.

[0038] The chromium, scandium and zinc metal elements are derived from waste extractants of a hydrometallurgical device, and the solution containing chromium, scandium and zinc salts recovered therefrom is an oxalate solution of Cr, Sc and Zn, wherein the preferred concentration of chromium oxalate is 20-40wt%, the preferred concentration of scandium oxalate is 10-25wt%, the preferred concentration of zinc oxalate is 1-3wt%, and the solvent includes water;

[0039] Specifically, the waste extractant of the hydrometallurgical device is produced during the extraction and enrichment of hydrometallurgical nickel. The crude nickel sulfate leaching solution (pre-extraction solution) contains impurity metal ions such as Cr, Sc, and Zn. The impurity metals in the extractant are continuously enriched during operation. Such impurity ions are difficult to strip, and eventually the extractant is poisoned and inactivated. The waste extractant is sold at a low price as valuable hazardous waste, and the cost of replacing the extractant is high. However, the waste catalyst usually contains 0.2-5wt% of Cr element; 0.1-3wt% of Sc element, and 0.01-0.3wt% of Zn element, which can be used as the precursor of the active component of the catalyst of the present invention. For example, a method for treating the waste extractant of a hydrometallurgical device to obtain an oxalate solution of Cr, Sc, and Zn is to mix the waste extractant with a sodium hydroxide solution, heat and stir, filter, wash, and dry to obtain a metal hydroxide slag containing Cr, Sc, and Zn, and then mix and react with oxalic acid, filter and obtain a clear liquid, and prepare;

[0040] Preferably, the mass ratio of the waste extractant to the sodium hydroxide solution is 1:0.5-5, preferably 1:1-2, and the concentration of the sodium hydroxide solution is 5-10wt%; preferably, the heating temperature is 70-100°C, and the time is 2-4h; preferably, the drying temperature is 100-150°C, and the time is 5-10h; preferably, the mass ratio of the metal hydroxide slag to oxalic acid is 2-10:1, preferably 3-5:1; preferably, the reaction temperature is 60-100°C, and the time is 1-4h.

[0041] Preferably, the mass ratio of the oxalate solution of Cr, Sc and Zn to the carrier is 0.06-0.5:1, preferably 0.2-0.4:1.

[0042] In a specific embodiment, the ultrasonic immersion time is 10-20 hours.

[0043] In a specific embodiment, the binder is selected from one or more of aluminum hydroxide dry glue, sesbania powder, and carboxymethyl cellulose, preferably carboxymethyl cellulose.

[0044] In a specific embodiment, the mass ratio of the catalyst precursor to the binder is 2-10:1.

[0045] In a specific embodiment, the calcination temperature is 250-500° C., and the calcination time is 3-8 hours.

[0046] The preparation method described above also includes operations such as mixing, tableting, grinding and screening, drying, and roasting, which are all conventional operations in the field and are not specifically required by the present invention.

[0047] In a third aspect, the present invention provides the use of the above hydrogenation catalyst.

[0048] The hydrogenation catalyst of the present invention is the hydrogenation catalyst described above, or the hydrogenation catalyst prepared by the method described above, which can be used for fixed-bed dinitrotoluene hydrogenation to toluenediamine.

[0049] The above-mentioned method for preparing toluenediamine by hydrogenation of dinitrotoluene can adopt existing processes and react through conventional reactors in the art. The relevant operations and process conditions in the preparation method of the present invention, and the devices used therein, can all be selected and carried out by corresponding conventional methods in the art, and there is no particular limitation thereto. The technicians can optimize the known processes in the prior art according to actual needs, and specifically, for example, the conditions listed in the following embodiments of the present invention can be adopted.

[0050] Specifically, a method for preparing toluenediamine by hydrogenating dinitrotoluene, the method using the hydrogenation catalyst of the present invention, the steps comprising:

[0051] Hydrogenation catalyst reduction: The catalyst is loaded into a fixed bed reactor and hydrogen is introduced at a hydrogen volume space velocity of 1200-2400 h -1 , temperature 200-400℃, reduction 4-8h.

[0052] Dinitrotoluene hydrogenation to toluenediamine: In a fixed bed reactor (such as a tubular fixed bed reactor) loaded with the above-mentioned post-reduction hydrogenation catalyst, dinitrotoluene and hydrogen are fed for reaction, the reaction pressure is 50-400 KPaG, the reaction temperature is 150-300°C, the molar ratio of hydrogen to dinitrotoluene is 20-40:1, and the reaction volume space velocity is 6h -1 , reaction time 4-8h.

[0053] Compared with the prior art, the present invention has the following advantages:

[0054] 1. The catalyst of the present invention adopts Ni and Cr active components to work synergistically, which improves the dispersion on the catalyst surface and inhibits the aggregation of Ni crystals of the single active component. At the same time, Sc and Zn additives are added to form alloy phases of Ni-Zn and Cr-Sc, which makes up for the disadvantage of catalyst deactivation due to competitive adsorption of tar heavy components at the active sites of the catalyst in the prior art.

[0055] 2. The method of the present invention can realize resource utilization of metal components in waste liquid of hydrometallurgical devices and waste catalyst slag of toluene diamine devices, reduce the production cost of the devices, and at the same time, the recovered metals can be used as catalyst active components.

[0056] 3. The present invention innovatively adopts alkaline solution stripping and oxalic acid reduction method to treat the waste extractant of hydrometallurgy, and at the same time, recycles the valuable metal components therein, and regenerates the extractant, so that the poisoned extractant can regain its ability to extract and purify crude nickel sulfate salt.

[0057] 4. The present invention optimizes the molecular sieve carrier, and uses sodium oleate to modify the surface of the carrier to modify the chemical properties of the carrier surface. The carrier exhibits a hydrophilic surface at room temperature, which is beneficial to the dispersion of active components in the catalyst preparation process; during the catalytic reaction, at a higher reaction temperature, the hydrophobicity of the catalyst surface is more inclined to the N=O adsorption mode, which is helpful for the timely desorption of toluenediamine molecules and improves the product selectivity. At the same time, the sodium oleate modifier is used to modify the thermosensitive polymer. The surface activity of the oleic acid group has the effect of reducing the viscosity of the reaction liquid, reducing the pressure drop of the catalyst bed, and avoiding the tar substances from staying on the catalyst surface and in the pores for too long, causing the catalyst to be carbonized and deactivated. Nano-silicon coating modifies the molecular sieve carrier, increases the number of active centers on the carrier surface and in the bulk phase, and helps to expose the metal active centers.

[0058] 5. The catalyst of the present invention is suitable for the production of toluenediamine by hydrogenation of dinitrotoluene in a fixed bed. The catalyst has high dinitrotoluene hydrogenation activity and toluenediamine selectivity and has good stability in the temperature range of 150-300°C. DETAILED DESCRIPTION

[0059] The present invention is described in more detail below in conjunction with the embodiments, but it should be noted that the following embodiments are not limiting examples of the scope of the present invention.

[0060] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The chemical reagents in the examples are all from Sinopharm Chemical Reagent Co., Ltd. and are analytically pure.

[0061] In the embodiment, the composition of toluenediamine, dinitrotoluene, etc. in the product was quantitatively analyzed by 7890A gas chromatograph of Agilent Company of the United States. FID detector and DB-5 chromatographic column were used, the injection port temperature was 280°C, the detector temperature was 280°C, the carrier gas (nitrogen) flow rate was 3ml / min, the air flow rate was 400ml / min, and the hydrogen flow rate was 40ml / min.

[0062] Catalyst Characterization:

[0063] The pore structure properties of the catalyst were analyzed using the Tristar 3020 mesoporous physical adsorption instrument produced by Micromeritics, USA. The measurement type was full-pore measurement. The sample was dried, degassed in a vacuum state at 300°C for 8 hours, and then subjected to liquid nitrogen adsorption and desorption. The specific surface area of ​​the catalyst was obtained using the BET method, and the pore structure data of the sample was calculated using the BJH method.

[0064] The particle size and distribution of the active component Pt crystals were measured using a JEM-2100UHR transmission electron microscope produced by Japan Electronics Corporation.

[0065] The waste extractant comes from the hydrometallurgical unit of Wanhua Chemical Yantai Industrial Park. The waste extractant contains 0.2-0.5wt% Cr, 0.1-0.3wt% Sc and 0.01-0.05wt% Zn.

[0066] The nickel-based waste catalyst comes from the toluene diamine unit of Wanhua Chemical Yantai Industrial Park, and the Ni content in the waste catalyst is 20-60wt%.

[0067] The present invention adopts a tubular fixed bed reactor to evaluate the activity of the hydrogenation catalyst.

[0068] Example 1

[0069] Preparation of hydrogenation catalyst 1#:

[0070] 1) Weigh 30g of Y-type molecular sieve and place it in a gas phase reactor, introduce a trisilane and nitrogen mixed gas at a rate of 300ml / min, the volume ratio of trisilane to nitrogen is 0.2, maintain the reaction temperature at 800°C and the pressure at 0.5MPaG for vapor deposition reaction, the reaction time is 60min, and a nano-silicon coated molecular sieve carrier is obtained;

[0071] 3 g of isopropyl acrylamide was dissolved in water to prepare a solution with a concentration of 50 wt %. 30 g of the prepared nano-silicon-coated molecular sieve was dispersed therein. 1.5 g of ammonium persulfate and 1.5 g of sodium oleate were added and stirred under argon protection. After filtering, washing and vacuum drying, a nano-silicon-coated molecular sieve carrier modified by sodium oleate and a thermosensitive polymer was obtained.

[0072] 2) Weigh 30g of nickel-based waste catalyst, add 15g of oxalic acid, mix and stir, heat to 90°C and maintain the reaction for 1h, filter and collect the clear liquid to obtain a nickel oxalate solution, wherein the nickel oxalate concentration is 40wt%, and the solvent includes water;

[0073] Weigh 30g of hydrometallurgical waste extractant, add 15g of 8wt% sodium hydroxide aqueous solution, mix and stir, heat to 80°C and maintain for 1h, filter the residue, wash and dry, weigh 15g of the dried residue, add it to 7.5g of oxalic acid, mix and stir, heat to 90°C and maintain the reaction for 2h, filter the clear liquid to obtain Cr, Sc, and Zn oxalate solutions, wherein the concentration of chromium oxalate is 20wt%, the concentration of scandium oxalate is 10wt%, the concentration of zinc oxalate is 1wt%, and the solvent includes water.

[0074] 3) 20 g of nickel oxalate solution, 2 g of oxalate solution of Cr, Sc and Zn and 30 g of the prepared sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier were mixed, and the mixture was ultrasonically impregnated for 18 h and dried to obtain a catalyst precursor;

[0075] 30 g of the catalyst precursor was mixed evenly with 6 g of aluminum hydroxide dry gel, pressed into tablets, ground and sieved to obtain 20-40 mesh molecular sieve particles, and calcined at 350° C. for 5 h to obtain hydrogenation catalyst 1#.

[0076] Based on the total weight of the catalyst, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier accounts for 89.28wt%; the content of the metal active components loaded on the carrier, calculated as metal elements, is Ni 10wt%, Cr 0.5wt%, Sc 0.2wt%, and Zn 0.02wt%.

[0077] The specific surface area is 552 m 2 / g, average pore size 30nm, TEM test, the average particle size of the catalyst active component Ni is 4nm, the average particle size of Cr is 3nm.

[0078] Comparative Example 1

[0079] The method of Example 1 was followed, except that step 1) was omitted, an unmodified Y-type molecular sieve was used as the carrier, and other operations and conditions remained unchanged to obtain hydrogenation catalyst 1-1#.

[0080] Based on the total weight of the catalyst, the molecular sieve carrier accounts for 89.28wt%; the contents of the metal active components loaded on the carrier, calculated as metal elements, are Ni 10wt%, Cr 0.5wt%, Sc 0.2wt%, and Zn 0.02wt%.

[0081] The specific surface area is 430 m 2 / g, average pore size 27nm, TEM test, the average particle size of the catalyst active component Ni is 5nm, and the average particle size of Cr is 4nm.

[0082] Example 2

[0083] Preparation of hydrogenation catalyst 2#:

[0084] 1) Weigh 30g of Y-type molecular sieve and place it in a gas phase reactor, introduce a mixture of trisilane and nitrogen at a rate of 300ml / min, the volume ratio of trisilane to nitrogen is 0.5, maintain the reaction temperature at 1000°C and the pressure at 1MPaG for vapor deposition reaction, and the reaction time is 90min to obtain a nano-silicon coated molecular sieve carrier;

[0085] 300g of isopropyl acrylamide was dissolved in water to prepare a solution with a concentration of 80wt%, 30g of the prepared nano-silicon coated molecular sieve was dispersed therein, 60g of ammonium persulfate and 30g of sodium oleate were added, and the solution was stirred under argon protection. After filtering, washing and vacuum drying, a nano-silicon coated molecular sieve carrier modified by sodium oleate and a thermosensitive polymer was obtained.

[0086] 2) Weigh 30g of nickel-based waste catalyst, add 3g of oxalic acid, mix and stir, heat to 100°C and maintain the reaction for 4h, filter and take the clear liquid to obtain a nickel oxalate solution, wherein the nickel oxalate concentration is 55wt%, and the solvent includes water;

[0087] Weigh 30g of hydrometallurgical waste extractant, add 150g of 8wt% sodium hydroxide aqueous solution, mix and stir, heat to 90°C and maintain for 2h, filter out the residue, wash and dry, weigh 15g of the dried residue, add it to 1.5g of oxalic acid, mix and stir, heat to 90°C and maintain the reaction for 2h, filter out the clear liquid, and obtain Cr, Sc, and Zn oxalate solutions, wherein the concentration of chromium oxalate is 40wt%, the concentration of scandium oxalate is 25wt%, the concentration of zinc oxalate is 3wt%, and the solvent includes water.

[0088] 3) 90 g of nickel oxalate solution, 15 g of Cr, Sc, and Zn oxalate solution and 30 g of the prepared sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier were mixed, and the mixture was ultrasonically impregnated for 18 h and dried to obtain a catalyst precursor;

[0089] 30 g of the catalyst precursor was mixed evenly with 10 g of aluminum hydroxide dry gel, pressed into tablets, ground and sieved to obtain 20-40 mesh molecular sieve particles, and calcined at 450° C. for 8 h to obtain hydrogenation catalyst 2#.

[0090] Based on the total weight of the catalyst, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier accounts for 51.7wt%; the content of the metal active components loaded on the carrier, calculated as metal elements, is Ni 40wt%, Cr 5wt%, Sc 3wt%, and Zn 0.3wt%.

[0091] The specific surface area is 531m 2 / g, average pore size 28nm, TEM test, the average particle size of the catalyst active component Ni is 4nm, the average particle size of Cr is 4nm.

[0092] Comparative Example 2

[0093] Referring to the method of Example 2, except that isopropyl acrylamide, ammonium persulfate and sodium oleate are not added in the carrier preparation process, other operations and conditions remain unchanged, to obtain hydrogenation catalyst 2-1#, wherein the carrier is a nano-silicon coated molecular sieve carrier.

[0094] Based on the total weight of the catalyst, the nano-silicon coated molecular sieve carrier accounts for 51.7wt%; the content of the metal active components loaded on the carrier, calculated as metal elements, is Ni 40wt%, Cr 5wt%, Sc 3wt%, and Zn 0.3wt%.

[0095] The specific surface area is 520 m 2 / g, average pore size 22nm, TEM test, the average particle size of the catalyst active component Ni is 5nm, and the average particle size of Cr is 4nm.

[0096] Example 3

[0097] Preparation of hydrogenation catalyst 3#:

[0098] 1) Weigh 30g of Y-type molecular sieve and place it in a gas phase reactor, introduce a trisilane and nitrogen mixed gas at a rate of 300ml / min, the volume ratio of trisilane to nitrogen is 2, maintain the reaction temperature at 1000°C and the pressure at 0.8MPaG for vapor deposition reaction, and the reaction time is 50min to obtain a nano-silicon coated molecular sieve carrier;

[0099] 30g of isopropyl acrylamide was dissolved in water to prepare a solution with a concentration of 70wt%, 30g of the prepared nano-silicon coated molecular sieve was dispersed therein, 6g of ammonium persulfate and 6g of sodium oleate were added, and the solution was stirred under argon protection. After filtering, washing and vacuum drying, a nano-silicon coated molecular sieve carrier modified by sodium oleate and a thermosensitive polymer was obtained.

[0100] 2) Weigh 30g of nickel-based waste catalyst, add 6g of oxalic acid, mix and stir, heat to 70°C and maintain the reaction for 3h, filter and take the clear liquid to obtain a nickel oxalate solution, wherein the nickel oxalate concentration is 50wt%, and the solvent includes water;

[0101] Weigh 30g of hydrometallurgical waste extractant, add 60g of 8wt% sodium hydroxide aqueous solution, mix and stir, heat to 100°C and maintain for 4h, filter out the residue, wash and dry, weigh 15g of the dried residue, add it to 3g of oxalic acid, mix and stir, heat to 90°C and maintain the reaction for 2h, filter out the clear liquid to obtain Cr, Sc, and Zn oxalate solutions, wherein the concentration of chromium oxalate is 35wt%, the concentration of scandium oxalate is 22wt%, the concentration of zinc oxalate is 2.5wt%, and the solvent includes water.

[0102] 3) 38 g of nickel oxalate solution, 7 g of Cr, Sc, and Zn oxalate solution, and 30 g of the prepared sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier were mixed, and the mixture was ultrasonically impregnated for 18 h and dried to obtain a catalyst precursor;

[0103] 30 g of the catalyst precursor was mixed evenly with 10 g of aluminum hydroxide dry gel, pressed into tablets, ground and sieved to obtain 20-40 mesh molecular sieve particles, and calcined at 450° C. for 8 h to obtain hydrogenation catalyst 3#.

[0104] Based on the total weight of the catalyst, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier accounts for 75.85wt%; the content of the metal active components loaded on the carrier, calculated as metal elements, is Ni 20wt%, Cr 2.5wt%, Sc 1.5wt%, and Zn 0.15wt%.

[0105] The specific surface area is 560 m 2 / g, average pore size 34nm, TEM test, the average particle size of the catalyst active component Ni is 4nm, the average particle size of Cr is 3nm.

[0106] Comparative Example 3

[0107] Referring to the method of Example 3, the difference is that the waste extractant is not introduced into the catalyst preparation process, that is, the Cr, Sc, and Zn metal elements in the waste extractant are not mixed into the catalyst, and other operations and conditions remain unchanged to obtain hydrogenation catalyst 3-1#, in which the carrier is a nano-silicon coated molecular sieve.

[0108] Based on the total weight of the catalyst, the nano-silicon coated molecular sieve carrier accounts for 80wt%; the content of the metal active component loaded on the carrier is Ni 20wt% in terms of metal elements.

[0109] The specific surface area is 565m 2 / g, the average pore size is 37nm, and according to TEM test, the average particle size of the catalyst active component Ni is 4nm.

[0110] Application Examples

[0111] The hydrogenation performance of the hydrogenation catalysts prepared in the above examples and comparative examples was tested using a tubular fixed bed reactor, and the test conditions were as follows:

[0112] (1) Loading the prepared hydrogenation catalyst into the middle section of the fixed bed reactor, with a loading amount of 10 ml;

[0113] (2) Hydrogen was introduced at a flow rate of 300 mL / min and a volumetric space velocity of 0.5 h -1 , temperature 300℃, reduce the catalyst for 8h;

[0114] (3) Dinitrotoluene and hydrogen were introduced into the reactor, the feed rate of dinitrotoluene was 1 ml / min, the feed rate of hydrogen was 6 NL / min, and the molar ratio of hydrogen to dinitrotoluene was 30:1. The reaction pressure was controlled at 400 KPaG by the hydrogen flow rate, the reaction temperature was adjusted at 300°C by heat transfer oil, and the reaction time was 8 h.

[0115] The reaction products were analyzed and the results are shown in Table 1:

[0116] Table 1 Example Comparative Example Reaction Products

[0117] Conversion rate / % Selectivity / % Tar content / wt% Example 1 99.53 95.43 0.22 Comparative Example 1 97.85 93.65 0.85 Example 2 99.03 95.13 0.64 Comparative Example 2 98.25 94.15 1.38 Example 3 99.59 95.29 0.14 Comparative Example 3 97.50 92.50 2.13

[0118] As can be seen from the table, the active components such as Ni, Cr, and Sc in the waste catalyst and waste extractant are recovered from the nano-silicon coated molecular sieve carrier modified by sodium oleate-modified thermosensitive polymer. The synergistic effect of multiple active components improves the dispersion on the catalyst surface, inhibits the aggregation of single active component Ni crystals, increases the number of active centers on the carrier surface and in the bulk phase, and greatly improves the conversion rate of nitroxylene. In the catalyst 3-1# experiment prepared with only nickel oxalate as the nickel source, the conversion rate of dinitrotoluene is about 97.5%, and the hydrogenation performance is much lower than that of the resource recovery of multi-metal active component catalysts.

[0119] Nano-silicon coated molecular sieve catalyst modified by sodium oleate-modified thermosensitive polymer can effectively improve the selectivity of toluenediamine and reduce the content of by-products such as tar; in the experiment of catalyst 1-1# without modified molecular sieve carrier, the selectivity of toluenediamine is 93.65%, in the experiment of catalyst 2-1# without adding sodium oleate and isopropyl acrylamide to adjust the thermosensitive properties of the carrier, the selectivity of toluenediamine is 94.15%, and in the experiment of modified carrier catalyst 2#, the selectivity of toluenediamine is >95%.

Claims

1. A hydrogenation catalyst, characterized in that The catalyst comprises a nano-silicon coated molecular sieve carrier modified by sodium oleate-modified thermosensitive polymer, and a metal active component loaded on the carrier, wherein the metal active component comprises Ni, Cr, Sc, Zn or oxides thereof.

2. The hydrogenation catalyst according to claim 1, characterized in that Based on the total weight of the catalyst, the sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier accounts for 50-90wt%; The content of the metal active component loaded on the carrier is calculated as metal elements, respectively: Ni 10-40wt%, preferably 20-30wt%; Cr 0.2-5wt%, preferably 1-3wt%; Sc 0.1-3wt%, preferably 0.5-1wt%; Zn 0.01-0.3wt%, preferably 0.05-0.1wt%; and / or The hydrogenation catalyst has a specific surface area of ​​400-800m 2 / g, pore size of 25-50nm; and / or In the hydrogenation catalyst, the grain size of the metal active component Ni is 1-5 nm, and the grain size of Cr is 2-7 nm.

3. The hydrogenation catalyst according to claim 1, characterized in that The sodium oleate-modified thermosensitive polymer-modified nano-silicon-coated molecular sieve carrier is prepared by the following method, which comprises the following steps: (1) placing the molecular sieve in a gas phase reactor, introducing trisilane and nitrogen, maintaining a certain temperature and pressure for vapor phase deposition reaction, and obtaining a nano-silicon coated molecular sieve carrier; (2) dispersing the nano-silicon coated molecular sieve carrier in an aqueous solution of isopropyl acrylamide, adding ammonium persulfate and sodium oleate, stirring under the protection of an inert atmosphere, filtering, washing and drying to obtain a nano-silicon coated molecular sieve carrier modified by a sodium oleate-modified thermosensitive polymer.

4. The hydrogenation catalyst according to claim 1, characterized in that The molecular sieve in step (1) is selected from one or more of 13X molecular sieve, Y molecular sieve, and ZSM-5 molecular sieve, preferably Y molecular sieve; and / or In step (1), the volume ratio of trisilane to nitrogen is 0.2-5:1, preferably 0.5-2:1, and the trisilane is converted into gas phase and then introduced into the gas phase reactor; and / or The vapor deposition reaction in step (1) is carried out at a temperature of 150°C-1500°C, a pressure of 0-1.0 MPaG, and a time of 10-90 min; and / or The mass ratio of the isopropyl acrylamide to the nano-silicon coated molecular sieve carrier in step (2) is 0.1-10:1, preferably 0.2-3:1; Preferably, the aqueous solution of isopropylacrylamide has a concentration of 50-80 wt %; and / or The mass ratio of the ammonium persulfate to the nano-silicon coated molecular sieve carrier in step (2) is 0.05-2:1, preferably 0.1-0.5:1; and / or In step (2), the mass ratio of the sodium oleate to the nano-silicon coated molecular sieve carrier is 0.05-1:1, preferably 0.1-0.5:

1.

5. A method for preparing the hydrogenation catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: A solution containing metal active elements is added to a nano-silicon coated molecular sieve carrier modified by a sodium oleate-modified thermosensitive polymer, and a catalyst precursor is obtained by ultrasonic impregnation and drying. The catalyst precursor and the binder are mixed evenly, pressed into tablets, ground and sieved, dried, and calcined to obtain the hydrogenation catalyst.

6. The preparation method according to claim 5, characterized in that: The metal active elements are nickel, chromium, scandium and zinc; and / or The salt solution containing metal active elements is a soluble salt solution of nickel, chromium, scandium and zinc, preferably an aqueous solution of nickel nitrate, chromium nitrate, scandium nitrate and zinc nitrate; and / or The salt solution containing metal active elements is a salt solution containing metal active elements obtained by resource recovery; Wherein, the nickel metal element is derived from the nickel-based waste catalyst, and the solution containing nickel salt recovered therefrom is a nickel oxalate solution, wherein the nickel oxalate preferably has a concentration of 40-55 wt%, and the solvent includes water; Preferably, the mass ratio of the nickel oxalate salt solution to the carrier is 0.6-3:1, preferably 1-2:

1. The chromium, scandium and zinc metal elements are derived from waste extractants of a hydrometallurgical device, and the solution containing chromium, scandium and zinc salts recovered therefrom is an oxalate solution of Cr, Sc and Zn, wherein the preferred concentration of chromium oxalate is 20-40wt%, the preferred concentration of scandium oxalate is 10-25wt%, the preferred concentration of zinc oxalate is 1-3wt%, and the solvent includes water; Preferably, the mass ratio of the Cr, Sc, Zn oxalate solution to the carrier is 0.01-0.5:1, preferably 0.2-0.5:

1.

7. The preparation method according to claim 6, characterized in that: The method for treating the nickel-based waste catalyst to obtain the nickel oxalate solution is to mix the waste catalyst with oxalic acid, heat and stir to react, filter and obtain the clear liquid, and prepare the solution; Preferably, the mass ratio of the waste catalyst to oxalic acid is 2-10:1, preferably 3-5:1; preferably, the heating temperature is 60-100°C; preferably, the reaction time is 1-4h; and / or The method for treating waste extractant of a hydrometallurgical device to obtain an oxalate solution of Cr, Sc and Zn is to mix the waste extractant with a sodium hydroxide solution, heat and stir, filter, wash and dry to obtain a metal hydroxide slag containing Cr, Sc and Zn, then mix and react with oxalic acid, filter and obtain a clear liquid to prepare; Preferably, the mass ratio of the waste extractant to the sodium hydroxide solution is 1:0.5-5, preferably 1:1-2, and the concentration of the sodium hydroxide solution is 5-10wt%; preferably, the heating temperature is 70-100°C, and the time is 2-4h; preferably, the drying temperature is 100-150°C, and the time is 5-10h; preferably, the mass ratio of the metal hydroxide slag to oxalic acid is 2-10:1, preferably 3-5:1; preferably, the reaction temperature is 60-100°C, and the time is 1-4h.

8. The preparation method according to claim 5, characterized in that: The ultrasonic immersion time is 10-20h; and / or The binder is selected from one or more of aluminum hydroxide dry glue, sesbania powder, and carboxymethyl cellulose, preferably carboxymethyl cellulose; and / or The mass ratio of the catalyst precursor to the binder is 2-10:1; and / or The calcination temperature is 250-500° C., and the calcination time is 3-8 hours.

9. Use of the hydrogenation catalyst according to any one of claims 1 to 4, or the hydrogenation catalyst prepared by the method according to any one of claims 5 to 8, in hydrogenating dinitrotoluene to produce toluenediamine.

10. A method for preparing toluenediamine by hydrogenating dinitrotoluene, characterized in that: The method uses the hydrogenation catalyst according to any one of claims 1 to 4, or the hydrogenation catalyst prepared by the method according to any one of claims 5 to 8, and the steps include: Hydrogenation catalyst reduction: The catalyst is loaded into a fixed bed reactor and hydrogen is introduced at a hydrogen volume space velocity of 1200-2400 h -1 , temperature 200-400℃, reduction 4-8h; Dinitrotoluene hydrogenation to toluenediamine: In a fixed bed reactor (such as a tubular fixed bed reactor) loaded with the above-mentioned post-reduction hydrogenation catalyst, dinitrotoluene and hydrogen are fed for reaction, the reaction pressure is 50-400 KPaG, the reaction temperature is 150-300°C, the molar ratio of hydrogen to dinitrotoluene is 20-40:1, and the reaction volume space velocity is 6h -1 , reaction time 4-8h.

Citation Information

Patent Citations

  • Preparation method and application of a catalyst for the hydrogenation of dinitrotoluene to toluenediamine

    CN107233887B